(untitled) (Archives of Criminology, 2024)
Restorative justice (RJ), despite its thriving development worldwide, remains a niche issue in Poland. The impact of RJ on individuals participating in it has been widely studied for years. Simultaneously, exploration into how restorative meetings actually work has only recently begun, aiming to design them to produce the best possible results. In this article, I address these very issues. I discuss and confront research on the theory of reintegrative shaming, procedural justice and concepts of readiness in the context of restorative justice. I analyze how these theories interact with each other, aiming to highlight the factors that influencing the outcomes of restorative meetings, including mediations. Based on the synthesis, I identify key areas for the development of the practice in Poland.